2006
DOI: 10.1161/01.atv.0000208365.45200.41
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin Gene Polymorphisms and Haplotypes and the Risk of Cardiovascular Events

Abstract: Background-Thrombomodulin is an anticoagulant expressed during endothelial activation and damage. To address the potential role of allelic variants of thrombomodulin gene in the pathogenesis of cardiovascular diseases, we analyzed in a prospective follow-up study 8 single-nucleotide polymorphisms (SNPs) across the thrombomodulin locus, covering all common (Ͼ5%) haplotypes. Methods and Results-Two separate, stratified random samples of men and women 25 to 74 years of age were examined in Finland in 1992 and 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 26 publications
2
22
1
Order By: Relevance
“…This finding is in keeping with three previous studies, which reported linkage disequilibrium between +1418C/T and -1208/-1209delTT [9,10,17].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in keeping with three previous studies, which reported linkage disequilibrium between +1418C/T and -1208/-1209delTT [9,10,17].…”
Section: Discussionsupporting
confidence: 93%
“…In the 148 incident brain infarctions, none of the SNPs and the corresponding haplotypes were associated with brain infarction, myocardial infarction or death [10]. In keeping with these results, we found no significant relationship between TM gene polymorphism and brain infarction risk even when analyses were restricted to subjects without a previous vascular history.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…35 As to the levels of sTM, our results indicate that increased levels are associated with higher VTE risk, and this association is, at least in part, independent of the THBD c.1418C>T polymorphism. Increased sTM levels have also been reported in patients with recurrent VTE.…”
Section: Discussionmentioning
confidence: 67%
“…25,35 . Furthermore, it has also been shown that THBD rs1042580, rs1962 and rs3176123 polymorphisms did not contribute significantly to the risk of cardiovascular events 23 . Another study shows that THBD rs1042580 polymorphism alone may not be a risk factor for cardiovascular events, however, in combination with polymorphisms in another gene involving coagulation pathway (Factor V gene), may contribute to risk for cardiovascular events 36 .…”
Section: Discussionmentioning
confidence: 99%